Real-time scale monitoring prototype of aircraft sys-tems through wireless communication - Awazacko Awazacko, Julián A.; Salazar Madrigal, Angélica M.; Galarza Bogotá, Cesar M.; Paz Penagos, Hernán (My University, 2023)
Currently, there are aircraft tracking systems known as ACARS (Aircraft Communication Addressing And Reporting System), which are already able to provide certain information, however, this can only be used in very specific contexts, since information such as passengers or fuel used do not serve much to the maintenance area if you want to provide real-time support. Therefore, this research proposed the development of a prototype capable of real-time monitoring some of the systems of an aircraft and thus deliver the necessary information for good maintenance, monitoring, and support in real-ti-me. For this case, the monitoring was performed on an RPAS (Remotely Piloted Aircraft System), since its acquisition or construction is more affordable; the flight prototype shed light on the behavior when acquiring and sending data frames inside the aircraft.

En la actualidad existen sistemas de seguimiento de aeronaves conocidos como ACARS (Aircraft Commu-nication Addressing And Reporting System), que ya son capaces de proporcionar cierta información, sin embargo esta solo puede ser usada en contextos muy específicos, puesto que información como pasaje-ros, combustible utilizado no sirven mucho al área de mantenimiento si se quisiera ofrecer un soporte en tiempo real, es por ello que esta investigación propuso el desarrollo de un prototipo que fuera capaz de monitorear en tiempo real algunos sistemas de una aeronave y así entregar la información necesaria para un buen mantenimiento, monitoreo y soporte en tiempo real, para este caso el monitoreo se hizo a un RPAS (Remotely Piloted Aircraft System) ya que su adquisición o construcción es más asequible, el proto-tipo de vuelo dio una idea del comportamiento al momento de realizar la adquisición y envío de tramas de datos dentro de la aeronave.
Prototipo de monitoreo a escala en tiempo real de los sistemas de una aeronave mediante comunicación ina-lámbrica
Digital
Keywords: Aeronaves; Aircraft; Comunicación - Investigaciones; Communication - Research; Telecomunicaciones; Telecommunication; Aircraft; monitoring prototy-pe; wireless communication; telecommunications; Aeronave; prototipo de moni-toreo; comunicación inalám-brica; telecomunicaciones